Epoxidation of olefins using a novel synthesized tungsten dendritic catalyst - Vieira, Eduardo G. [UNESP] (2017)
In this work, we carry out the preparation and characterization of new dendritic catalyst from an oligomer polyhedral silsesquioxane core (POSS-DG2.0). This material was used in the immobilization of the [W(CO)3Br2(NCMe)2] complex for optimization of the synthesis of the new dendritic catalyst. To determine the reaction time, the temperature effect and the amount of groups anchored in the material (mmol), some parameters, such as equilibration time and adsorption isotherms were studied. After the optimization studies and with the intention of application in catalysis, the new catalytic macromolecule was prepared by reaction of the dendrimer with the organometallic complex. The new catalyst was characterized by elemental analysis, FTIR, 13C and 29Si NMR, SEM, EDS, DRX and TGA. The new catalytic macromolecule POSS-DG2.0-[W(CO)3Br2] was tested in the epoxidation of olefins and proved to be an active catalyst with conversion rates between 60 and 88% and high selectivity in the formation of epoxides. To the best of our knowledge, this study is the first that has reported the preparation of POSS-DG2.0-[W(CO)3Br2] for catalytic epoxidation of 1-octene, cyclooctene, (S)-limonene, cis-3-hexen-1-ol, trans-3-hexen-1-ol and styrene.